2020
DOI: 10.14814/phy2.14618
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute, moderate intensity indoor cycling on the temporal resolution of human vision system, measured by critical fusion frequency

Abstract: Critical fusion frequency (CFF) reflects the basic temporal function of the visual system and therefore is a good measure of its performance. CFF has been implemented in psychological and pharmacological studies to evaluate cognitive functions. The influence of abnormal environmental conditions, such as physical exercise, has been recently explored. Previous studies have presented alterations of cognitive processes due to acute exercise. However, the duration of the effect after the end of exercise has not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(130 reference statements)
1
3
0
Order By: Relevance
“…Another study in cyclists described an increase in critical flicker frequency, a parameter indirectly indicative of optic nerve function. In this cohort, CFF increased immediately after training that was maintained 30 min post exercise which is in accordance with our observations regarding physiological restitution of the posterior pole after 15 minutes following high physical strain [ 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…Another study in cyclists described an increase in critical flicker frequency, a parameter indirectly indicative of optic nerve function. In this cohort, CFF increased immediately after training that was maintained 30 min post exercise which is in accordance with our observations regarding physiological restitution of the posterior pole after 15 minutes following high physical strain [ 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…Certain physiological stresses such as exercise or physical exhaustion may directly, but temporarily, affect an individual's CFF threshold [16][17][18]. It has also been suggested that CFF might be used as a measure for cortical arousal and central nervous system activity [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Certain physiological stresses such as exercise or physical exhaustion may directly, but temporarily, affect an individual’s CFF threshold [15, 16, 17]. It has also been suggested that CFF might be used as a measure for cortical arousal and central nervous system activity [18, 19, 20, 21].…”
Section: Introductionmentioning
confidence: 99%